Wear analysis of explanted conventional metal back polyethylene glenoid liners. (September 2018) - Kocsis, Gyorgy; Payne, Charlie J.; Wallace, Angus; McNally, Donal
Highlights: Volumetric assessment of conventional total shoulder replacement glenoid liner wear rate and scanning electron microscopy was accomplished. Coherence scanning interferometry (white light scanner) 3D images were acquired. This method requires no physical contact, ionising radiation or extensive surface preparation. The method has been validated against implant weight loss measurements. The volumetric wear rate was found to be more than twice as fast as in the case of total hip replacement with the acetabular liner made of the same type of polyethylene. Scanning electron microscopy images showed that the polyethylene was wearing in laminar flakes which indicated fatigue wear. Abstract: Introduction: Glenoid component wear and loosening is the Achilles heel of total shoulder replacement. Analysis of failed, revised implants might give an insight into the causes of component failure. Volumetric assessment of conventional total shoulder replacement glenoid liner wear rate and scanning electron microscopy was accomplished in this study for the purpose. Coherence scanning interferometry (white light scanner) 3D images were acquired. This method requires no physical contact, ionising radiation or extensive surface preparation. Methods: Twenty-four Nottingham total shoulder replacement system metal - back glenoid liners were explanted from revision shoulder arthroplasty cases. A Phase Vision Quartz DBE 800 scanner was used to scan the explanted polyethylene liners. The images of worn liners were registered to the reference image. Differences in wear and wear rate were quantified and central and non-central wear groups were distinguished. The Central wear group had a polyethylene wear rate of 115 ± 55mm3/year (mean ± SD). The non-central group showed a wear rate of 112 ± 42 mm3/year (mean ± SD), which was not significantly different from the central wear group (p = 0.426) Polyethylene liners showing edge wear from unstable shoulder replacements showed a wear rate of 545 mm 3 /year. Scanning electron microscopy images showed that the polyethylene was wearing in laminar flakes which indicated fatigue wear. Conclusion: The volumetric wear rate was found to be more than twice as fast as in the case of total hip replacement with the acetabular liner made of the same type of polyethylene. Use of coherence scanning interferometry is proposed for wear analysis.